The A-rray: visual animation in learning structured programming / Wan Salfarina Wan Husain ,Siti Hasrinafasya Che Hassan and Wan Norliza Wan Bakar - Wan Husain, Wan Salfarina; Che Hassan, Siti Hasrinafasya; Wan Bakar, Wan Norliza (Unit Penerbitan UiTM Kelantan, 2018)
In mastering computer programming language, the logical thinking skills have been proposed as a fundamental knowledge. Unfortunately, the logical reasoning among UiTM students in computer problem solving usually results in high failure rates. Thus, there is a need to find alternative solutions to improve the students' logical thinking skill in computer problem solving. The visual animation is considered to be a very promising potential to aid students in learning and understanding the algorithm concept in programming. According to the result of students' learning style by using a set of Learning Style Inventory, 54% of students are visual thinkers. Thus, this paper is proposing a conceptual model in developing an interactive multimedia courseware named The A-rray to reinforce the basic concepts of programming such as summation, average, counting and searching. The ADDIE model of instructional design was used to develop the application.